2010
DOI: 10.1007/s11258-010-9730-0
|View full text |Cite
|
Sign up to set email alerts
|

Large acorns benefit seedling recruitment by satiating weevil larvae in Quercus aliena

Abstract: Plants can enhance their seed viability and survival through reducing the fitness costs of herbivory by satiating seed predators at either plant or seed level, or both. The former satiates with production of large crops while the latter with large-sized seeds, enhancing the probability of seed survival. We analyzed both types of satiation in the interaction between the Quercus aliena and the weevil Curculio spp in 2 years with different crop size and acorn size. Larger crop size seemed to satiate less effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…In many cases, infested seeds can germinate, although the resulting seedlings may be less vigorous than their uninfested counterparts (Espelta, Bonal & Sánchez Humanes, 2009a;Espelta et al, 2009b;Yi & Yang, 2010;Dalgleish, Shukle & Swihart, 2012). In some cases, insect larvae may also represent a valuable food source in their own right.…”
Section: (7) Perishability: Dormancy and Infestationmentioning
confidence: 99%
“…In many cases, infested seeds can germinate, although the resulting seedlings may be less vigorous than their uninfested counterparts (Espelta, Bonal & Sánchez Humanes, 2009a;Espelta et al, 2009b;Yi & Yang, 2010;Dalgleish, Shukle & Swihart, 2012). In some cases, insect larvae may also represent a valuable food source in their own right.…”
Section: (7) Perishability: Dormancy and Infestationmentioning
confidence: 99%
“…Although loss of nutritional reserves caused by partial seed predation exerts negative effects on seed germination and seedling performance (Westoby et al 1992;Bonal et al 2007;Hou et al 2010), it has been widely demonstrated that partially eaten acorns can germinate and develop into normal seedlings provided the vulnerable embryonic parts successfully escape predation of animals (Andersson and Frost 1996;Branco et al 2002;Xiao et al 2007;Pérez et al 2008;Hou et al 2010;Yi and Yang 2010a;Perea et al 2011a). Therefore, partial consumption of acorns may play an alternative role in shaping seed dispersal patterns and oak regeneration processes.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, partial consumption of the basal end of acorns by animals has mainly found in the section of Lobatae, Cerris, and Mesobalanus in subgenera of Quercus (Steele et al 1993(Steele et al , 1996(Steele et al , 1998Dunning et al 2002;Hou et al 2010;Perea et al 2011a;Yi and Yang 2010b); there are few reports on white oak species (section Quercus) (Yi and Yang 2010a). Our field observations indicate that wood mice and Siberian chipmunks selectively consume the basal portion of Quercus mongolica acorns, and the partially consumed acorns are more frequently left on the surface rather than cached, especially in the mast years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the embryo remains alive) in partially predated seeds is strongly affected by seed size (Espelta et al 2009a) and embryo size, both within and among species (Perea et al 2018). Larger seeds, indeed, increase the likelihood of embryo survival as they satiate animals more easily (Mack 1998, Bonal et al 2007, Yi and Yang 2010. However, predator satiation by larger seeds might be precluded by higher levels of multi-larvae infestation (Bonal et al 2007) where more than one larva develops within the same seed (Bonal et al 2007, Fox et al 2012.…”
Section: Introductionmentioning
confidence: 99%